A Portable Intra-Operative Framework Applied to Distal Radius Fracture Surgery - Magaraggia, Jessica; Wei, Wei; Weiten, Markus; Kleinszig, Gerhard; Vetter, Sven; Franke, Jochen; Barth, Karl; Angelopoulou, Elli; Hornegger, Joachim (MICCAI 2015, 2015)
Fractures of the distal radius account for about 15% of all extremity fractures. To date, open reduction and internal plate fixation is the standard operative treatment. During the procedure, only fluoroscopic images are available for the planning of the screw placement and the monitoring of the instrument trajectory. Complications arising from malpositioned screws can lead to revision surgery. With the aim of improving screw placement accuracy, we present a prototype framework for fully intra-operative guidance that simplifies the planning transfer. Planning is performed directly intra-operatively and expressed in terms of screw configuration w.r.t the used implant plate. Subsequently, guidance is provided solely by a combination of locally positioned markers and a small camera placed on the surgical instrument that allows real-time position feedback. We evaluated our framework on 34 plastic bones and 3 healthy forearm cadaver specimens. In total, 146 screws were placed. On bone phantoms, we achieved an accuracy of 1.02 +/- 0.57mm, 3.68 +/- 4.38 degrees and 1.77 +/- 1.38 degrees in the screw tip position and orientation (azimuth and elevation) respectively. On forearm specimens, we achieved a corresponding accuracy of 1.63 +/- 0.91mm, 5.85 +/- 4.93 degrees and 3.48 +/- 3.07 degrees. Our analysis shows that our framework has the potential for improving the accuracy of the screw placement compared to the state of the art.